Effectiveness of Sea Turtle Conservation Management at the Turtle Conservation and Education Center of Serangan, Denpasar Bali - Taurus Zeno Adi Eti Harnino; I Nyoman Yoga Parawangsa; Luthfiana Aprilianita Sari; Sulastri Arsad (Journal of Marine and Coastal Science, 2021)
Turtles are one of the reptile animals that can migrate long distances along the Indian Ocean, Pacific Ocean and Southeast Asia. The purpose of turtle migration is to mate, find spawning locations and to find food. Sea turtles have an important role in maintaining the balance of the marine ecosystem. However, the high utilization of sea turtles by humans causes the turtle population to decline. One of the conservation sites that help the government program is in Serangan, Denpasar Bali, namely the TCEC (Turtle Conservation and Education Center), where there are several types of turtles such as the lekang turtle, hawksbill and green turtle. Data collection techniques in this study used observation methods including beach monitoring, relocation of turtle eggs to semi-natural hatchery hatching, hatchling and turtle nesting as well as measurement of turtle length and width carapase curve (CCL/CCW), sand temperature, nest depth, nest diameter, nest distance and nest calculation of the number of eggs to see the success of hatching. The results are turtle conservation activities, ranging from turtle maintenance, hatching of turtle eggs, relocation of eggs, and maintenance of hatchlings to release turtles. The effectiveness given by TCEC to manage and preserve the existence of sea turtles in Indonesia, especially in the Bali region is to provide awareness to the community by not consuming eggs and turtle meat.